(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article is written as a methodological recommendation for teachers and students. From the main sections of mathematics, information is given about ASL. The main properties of reflection as a result of the study of this topic by the reader his interest in the topic increases. We also tried to show examples of the main properties of this reflection in this article on this topic. The article serves to improve the effectiveness of teaching mathematics.We hope that this article will appeal to you.